Accounting Chamber – the leading institution in the financial and control activity of the state - Койчева, Ольга Семенівна; Койчева, О. С.; Койчева, Ольга Семеновна; Koicheva, Olha S. (Riga : Izdevniecība “Baltija Publishing”, 2020)
The article is devoted to the study of the Accounting Chamber as a leading institution in the financial control activities of the state. Issues related to the origin of financial control and its inseparable connection with state control are revealed. It is proved that despite the large number of bodies exercising financial control, it is impossible to state its effectiveness and efficiency, due to the lack of the normative act, which would define the system of financial control bodies and delimit the competence of such bodies to avoid duplication of powers. The issues of competence and implementation of the powers of the Accounting Chamber as a body of financial control to achieve the goal set by the legislator are considered separately. The categories of «competence» and «powers», their relationship and interdependence in the activities of the body under study were analysed.

Стаття присвячена дослідженню Рахункової палати як провідного інституту у фінансовій контрольній діяльності держави. Розкриваються питання виникнення фінансового контролю та його нерозривного зв’язку з державним контролем. Доведено, що незважаючи на велику кількість органів, які здійснюють фінансовий контроль, неможливо констатувати його ефективність та дієвість через відсутність нормативного акта, який би визначав систему органів фінансового контролю та розмежував компетенцію таких органів задля уникнення дублювання повноважень. Окремо розглядаються питання компетенції та реалізації повноважень Рахункової палати як органу фінансового контролю для досягнення поставленої законодавцем мети. Проаналізовано категорії «компетенція» та «повноваження», їх взаємозв’язок та взаємозалежність у діяльності досліджуваного органу.
Koicheva O. S. Accounting Chamber – the leading institution in the financial and control activity of the state / O. S. Koicheva // Public administration under modern conditions: concept, features, challenges : Collective monograph. - Riga : Izdevniecība “Baltija Publishing”, 2020. - P. 232-248.
Keywords: Accounting Chamber; financial control; financial control bodies; Рахункова палата; фінансовий контроль; органи фінансового контролю; Research Subject Categories::LAW/JURISPRUDENCE::Public law